Rhetorical moves and persuasive language in English and Arabic online skin care products advertisements / Eatidal Khalefa A Hasen - Eatidal Khalefa , A Hasen (2018)
Advertising communication is defined as “a social activity which functions in our cul-ture in order to facilitate the selling of products and/or services” (Fuertes-Olivera et al.2001, p. 1294). Adopting genre analysis in this study aids in identifying the social func-tions of persuasion in online advertisements of skin care products; since they tend to fol-low particular conventions that make them distinguishable or predictable. These conven-tions share a general structure, whereby all of the texts comprise the same rhetorical ele-ments with similar linguistic features to achieve the intended communicative purpose, which is persuasion. This research aims to determine the rhetorical moves and persuasive linguistic features in both English and Arabic online advertisements, with the theme of skin care products. For this purpose, a corpus of 200 online advertisements was compiled (100 texts for each language). The collected data were analyzed in two phases; the rhe-torical moves and persuasive linguistic features. In the first phase, rhetorical moves were analysed based on the adapted frameworks by Bhatia (2004), Kathaplia (1992) and Lab-rador et al. (2014). For the second phase, this study based on similar persuasive linguistic features from related studies (Ahanger & Dastuj, 2016; Bhatia, 1993; Cook, 2001; Cuddon, 2013; Delin, 2000; Fairclough, 1992; Fuertes-Oliver et al., 2001; Hermeren, 1999; Janoschka, 2004; Kubicova, 2013; Laborador et al., 2004; Lapsanska, 2006; Leech 1966; Linghong, 2006; Pilatova, 2015; Romanenko, 2014; Rush, 1998; Tanaka, 1994). The findings revealed that English online advertisements for skin care products consist of three prominent moves: ‘identifying product and purpose’, ‘describing the product’ and ‘urging action’. Meanwhile, Arabic online advertisements for skin care products con-sist of three prominent moves: ‘identifying product and purpose’, ‘describing the product’and ‘justifying the product. They also demonstrated the use of various persuasive linguis-tic features in the selected persuasive sub-step ‘evaluating the product positively’, as well as the persuasive moves ‘justifying the product’, ‘testimonials’, and ‘establishing creden-tials’. These persuasive linguistic features are syntactic (i.e. personal pronouns, rhetorical questions, multiple modification, non-finite clauses and adjectives, semantic (personifi-cation, metaphor, simile and hyperbole) and discoursal (emphatic enumerative).